Transaction Costs In Forming Milled Dry Grain Prices In West Java Province - Januar Arifin Ruslan; Abdul Mutolib; Dira Asri Pramita; Faqihuddin Faqihuddin (Cita konsultindo, 2024)
Transaction costs are part of institutional economics that have an economic impact on farmers. This research analyzes transmission of transaction costs in the formation of prices for farmers milled dry grain in West Java Province. Samples in this research are cities and districts in West Java Province. The data are price of milled dry grain and transaction costs which were analyzed using panel data regression. This research found a transaction costs had no effect on price of milled dry grain rice in West Java Province. Changes in transaction costs are not transmitted in formation of milled dry grain prices in short and long term. Determination of government purchasing prices has not been effective in determining the price of grain at the farmer level and given to the market.